FcRn-Driven Nanoengineered Mucosal Vaccine with Multi-Epitope Fusion Induces Robust Dual Immunity and Long-Term Protection Against Brucella - Tingting Tian; Yuejie Zhu; Kaiyu Shang; Huidong Shi; Ruixue Xu; Mingzhe Li; Fuling Pu; Junyu Kuang; Jianbing Ding; Fengbo Zhang (Vaccines)
Background: Brucellosis poses a significant public health challenge, necessitating effective vaccine development. Current vaccines have limitations such as safety concerns and inadequate mucosal immunity. This study aims to develop an FcRn-targeted mucosal Brucella vaccine by fusing the human Fc domain with Brucella’s multi-epitope protein (MEV), proposing a novel approach for human brucellosis prevention. Methods: The study developed a recombinant antigen (h-tFc-MEV) through computational analyses to validate antigenicity, structural stability, solubility, and allergenic potential. Molecular simulations confirmed FcRn binding. The vaccine was delivered orally via chitosan nanoparticles in murine models. Immunization was compared to MEV-only immunization. Post-challenge assessments were conducted to evaluate protection against Brucella colonization. Mechanistic studies investigated dendritic cell activation and antigen presentation. Results: Computational analyses showed that the antigen had favorable properties without allergenic potential. Molecular simulations demonstrated robust FcRn binding. In murine models, oral delivery elicited enhanced systemic immunity with elevated serum IgG titers and amplified CD4+/CD8+ T-cell ratios compared to MEV-only immunization. Mucosal immunity was evidenced by significant IgA upregulation across multiple tracts. Long-term immune memory persisted for six months. Post-challenge assessments revealed markedly reduced Brucella colonization in visceral organs. Mechanistic studies identified FcRn-mediated dendritic cell activation through enhanced MHC-II expression and antigen presentation efficiency. Conclusions: The FcRn-targeted strategy establishes concurrent mucosal and systemic protective immunity against Brucella infection. This novel vaccine candidate shows potential for effective human brucellosis prevention, offering a promising approach to address the limitations of current vaccines.